2011
DOI: 10.1080/08841233.2011.615287
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Social Work Students' Attitudes Toward Research: Problems and Prospects

Abstract: This study examines the attitudes of graduate social work students toward research in the contexts of academic study, professional social work practice, and students' personal lives. The authors collected quantitative and qualitative data from MSW students (n = 102) at a major Canadian school of social work. Findings suggest that MSW students appreciate the value of research for their professional and personal lives. However, they are apprehensive about the process of learning research, and when faced with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 28 publications
3
25
0
1
Order By: Relevance
“…This could be attributed to several factors. Previous research has documented social work students' reluctance to engage in research and anxiety about learning requisite statistics and quantitative methods (Epstein, 1987;Forte, 1995;Morgenshtern, Freymond, Agyapong, & Greeson, 2011). Based on our teaching of 1st-year doctoral students, some lack basic numeracy skills.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to several factors. Previous research has documented social work students' reluctance to engage in research and anxiety about learning requisite statistics and quantitative methods (Epstein, 1987;Forte, 1995;Morgenshtern, Freymond, Agyapong, & Greeson, 2011). Based on our teaching of 1st-year doctoral students, some lack basic numeracy skills.…”
Section: Discussionmentioning
confidence: 99%
“…There is a sound and consistent evidence indicating positive role of attitude in students' learning style and academic involvement (Abu et al, 2010;Awang, 2013) and most importantly as a result of quantitative and correlational studies (Morgenshtern et al, 2011;Butt and Shams, 2013;Saeidinia et al, 2013). Realization of the fact that that student attitude may change in potency due to the educational experience, exposure and active participation in learning provides a strong premise for a longitudinal research.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Several factors have been found to facilitate a reduction in anxiety, an increase in confidence, and more positive attitudes of students towards research. For example, a research-friendly and supportive environment where students are able to see the relevance of research to social work practice, are able to practice applying the concepts to "real-life like" situations (e.g., case studies), and where the instructors enthusiastically bring in their own research are identified as key ingredients to teaching research methods to social work students (Bolin et al, 2012;Csiernik, Birnbaum, & Decker Pierce, 2010;Freymond et al, 2014;Morgenshtern et al, 2011).…”
Section: Barriers and Facilitators To Teaching Quantitative Methods Imentioning
confidence: 99%
“…Confidence and self-efficacy were included in the evaluation as previous research (Bolin et al, 2012;Freymond et al, 2014;Morgenshtern et al, 2011) found students' confidence and self-efficacy in using research methods to increase when the material is directly relevant to their profession, and when students are able to apply the material to "real-life" like situations; two specific aspects of this quantitative method curriculum.…”
Section: Questionnaire Constructionmentioning
confidence: 99%